Decoding β-Cyclocitral-Mediated Retrograde Signaling Reveals the Role of a Detoxification Response in Plant Tolerance to Photooxidative Stress. Issue 10 (27th September 2018) - D'Alessandro, Stefano; Ksas, Brigitte; Havaux, Michel
Abstract : β-Cyclocitral, generated in the chloroplast under high-light stress, mitigates photooxidative stress by recruiting the xenobiotic response involving SCL14, TGAII, and ANAC102 transcription factors. Abstract: When exposed to unfavorable environmental conditions, plants can absorb light energy in excess of their photosynthetic capacities, with the surplus energy leading to the production of reactive oxygen species and photooxidative stress. Subsequent lipid peroxidation generates toxic reactive carbonyl species whose accumulation culminates in cell death. β-Cyclocitral, an oxidized by-product of β-carotene generated in the chloroplasts, mediates a protective retrograde response that lowers the levels of toxic peroxides and carbonyls, limiting damage to intracellular components. In this study, we elucidate the molecular mechanism induced by β-cyclocitral in Arabidopsis thaliana and show that the xenobiotic detoxification response is involved in the tolerance to excess light energy. The involvement of the xenobiotic response suggests a possible origin for this pathway. Furthermore, we establish the hierarchical structure of this pathway that is mediated by the β-cyclocitral-inducible GRAS protein SCARECROW LIKE14 (SCL14) and involves ANAC102 as a pivotal component upstream of other ANAC transcription factors and of many enzymes of the xenobiotic detoxification response. Finally, the SCL14-dependent protective mechanism is also involved in the low sensitivity of young leaf tissues to high-light stress.